PLANETARIUM DI BANJARBARU - Sari, Yunita Ambar; Wastuty, Prima Widia (UNIVERSITAS LAMBUNG MANGKURAT, 2022)
Astronomy is one of the oldest sciences of human civilization. In the past, our ancestors navigated the sea using the stars as navigation and the sky as a determinant of the period of cultivation. Astronomy has provided many benefits to our life up to now. Nowadays, astronomical phenomenons are associated with certain beliefs and even the public at large does not yet understand why those occurred. It is very important to socialize Astronomy to support the rapid development of science and technology, so the planetarium can be the answer, as a bridge between humans and science. The architectural problem raised in this design were